Growth, nutrient utilization, and body composition of dairy calves fed milk replacers containing different amounts of protein(1) - Blome, R. M. (J Anim Sci, 2003)
Male Holstein calves <1 wk of age were allowed a 2-wk adaptation period after purchase, and then were blocked by BW and assigned randomly within block to either a baseline slaughter group or one of four experimental groups (n = 8 to 9 per group). Treatments were isocaloric milk replacers (12.5% solids) fed at 12% of BW that contained 16.1, 18.5, 22.9, or 25.8% CP (DM basis) from whey protein sources. After a 6-wk feeding period, all calves were slaughtered and the weights and chemical composition of the viscera-free carcasses (VFC; including head, hide, feet, and tail) were determined. Gain of BW (0.38, 0.45, 0.56, and 0.62 kg/d) and gain:feed ratio (0.51, 0.59, 0.71, and 0.78) increased linearly (P < 0.001) as dietary CP increased; rate of change in body length, wither height, and heart girth also increased linearly (P ≤ 0.05). Balance measurements conducted during wk 3 and 4 of the experimental period showed that both absorbed N (16.9, 20.0, 25.8, and 30.6 g/d) and retained N (7.6, 9.0, 13.2, and 15.6 g/d) increased linearly (P < 0.001) as dietary CP increased. Retained N as a percentage of absorbed N increased linearly (P < 0.01) as dietary CP increased (44.3, 44.7, 50.7, and 50.9%), whereas biological value was unaffected (71.1, 68.7, 69.5, and 67.3%; P = 0.26). Digestible energy and ME represented 94.5 and 89.7% of intake energy, respectively, and were not affected by dietary CP content. Plasma urea N concentration increased linearly (2.9, 3.3, 4.6, and 6.0 mg/dL) as dietary CP increased. Contents of water (68.2, 69.1, 70.2, and 70.5%; P < 0.001) and protein (19.6, 20.0, 20.0, and 20.2%; P < 0.10) in VFC increased linearly, whereas contents of fat (7.2, 6.2, 5.5, and 5.2%; P < 0.001) and ash (5.1, 5.2, 4.8, and 4.7%; P < 0.02) decreased linearly as dietary CP increased. Trends in visceral tissue composition were similar to those for VFC. The content of water in VFC tissue gain increased, whereas contents of fat and energy decreased, as dietary CP increased. Final VFC energy and gain of energy in VFC were not affected by dietary CP. At similar initial ME intakes, increasing dietary CP (i.e., increasing protein:energy) linearly increased ADG, gain:feed, N retention, and deposition of lean tissue in VFC, demonstrating that diet composition can markedly affect components of body growth in preruminant dairy calves.